Mechanisms of follow-up to the Programme of Action on Population and Development in the Countries of Latin America and the Caribbean (ECLAC SantiagoCL, 2001)
Analyses the results of a survey conducted by the Latin American and Caribbean Demographic Centre (CELADE) - Population Division of ECLAC in the framework of activities underway to develop systems of indicators for follow-up to the Programme of Action on Population and Development.
Keywords: POPULATION